3(2X^2 + 6X +3) = 6X^2 + 18X + 9 This is the quadratic equation aX^2 + bX + C Where X is the unknown variable to be resolved, and a,b,c are constants Soluttion: X 1,2 3(2X^2...

3*(2x^2+6x+3) (answer)

3(2X^2 + 6X +3) = 6X^2 + 18X + 9 This is the quadratic equation aX^2 + bX + C Where X is the unknown variable to be resolved, and a,b,c are constants Soluttion: X 1,2 3(2X^2...

Set the following: A = number of apples Sally brought home P = number of plums Sally brought home Sally returned home with two times the number of plums than apples. So: P = 2A Cost of each apple = 50 cents...

We need to find the length of each side of a triangle based on given ratio between the sides and the total length (perimeter) of the triangle given in ft. We can define a triangle ABC with 3 sides a b c. Let side a be the shortest side. (a = shortest side) Let side b be the middle...

Set the following: Length = L Width = W The length is twice the width: L = 2*W or: W = L/2 Perimeter: P = 60ft = 2*L + 2*W Substituting L for W in the perimeter equation gives: P = 60ft = 2*L + 2*(L/2)...

solving inequalities in algebra (answer)

5x-3 < 7 5x < 7+3 5x < 10 x < 2 2-x < x+6 -x - x < 6-2 -2x < 4 multiplying both sides of the equation by -1 gives: 2x < -4 x < -2